1996
DOI: 10.1139/v96-246
|View full text |Cite
|
Sign up to set email alerts
|

Absorption spectroscopy of (Ind)Ni(PPh3)X (Ind = indenyl, 1-Me-indenyl; X = Cl, Br, Me) and M(Ind)2 (M = Ni, Ru; Ind = indenyl)

Abstract: Abstract:The electronic structures of two types of transition metal indenyl complexes have been studied. The first type, a series of (Ind)Ni(PPh,)X compounds (Ind = indenyl, 1-Me-indenyl; X = C1, Br, Me) was investigated by absorption spectroscopy and Extended Huckel Molecular Orbital calculations. The energy differences between calculated levels are in good agreement with experimental band positions. For example, the lowest energy singlet-singlet band maximum for (Ind)Ni(PPh,)Cl is at 19 500 cm-I and the calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
6
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…, Ni−C1 > Ni−C2 > Ni−C3). Such nonsymmetrical Ni−Ind interactions, which seem to result in a “tilting” of the indenyl ligand, have also been observed in 1 5c and the related complex (Ind)Ni(PPh 3 )Cl 5a. In the latter compounds, this “sideways slippage” has been shown to be caused by the unequal trans influences of the pseudo-trans ligands PPh 3 and Cl.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…, Ni−C1 > Ni−C2 > Ni−C3). Such nonsymmetrical Ni−Ind interactions, which seem to result in a “tilting” of the indenyl ligand, have also been observed in 1 5c and the related complex (Ind)Ni(PPh 3 )Cl 5a. In the latter compounds, this “sideways slippage” has been shown to be caused by the unequal trans influences of the pseudo-trans ligands PPh 3 and Cl.…”
supporting
confidence: 79%
“…When equimolar quantities of (1-Me-Ind)Ni(PPh 3 )Cl, 1 , AgBF 4 , and PPh 3 are stirred in CH 2 Cl 2 , the bis(phosphine) cationic species [(1-Me-Ind)Ni(PPh 3 ) 2 ] + , 2 , is obtained in 90% yield (eq 1). This methodology can also be used to prepare cationic complexes bearing different phosphine ligands, such as [(1-Me-Ind)Ni(PPh 3 )(PMe 3 )] + , 3 .…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…Unless otherwise stated, the 1 H (400 MHz), 13 C{ 1 H} (100.56 and 75.44 MHz), and 31 P{ 1 H} (161.92 MHz) NMR spectra were recorded at ambient temperature; the IR spectra were recorded as KBr pellets. The Ni−Cl precursors IndNi(PPh 3 )Cl ( 1 ) and (1-Me-Ind)Ni(PPh 3 )Cl ( 2) were prepared as described elsewhere. 4a,b …”
Section: Methodsmentioning
confidence: 99%
“…We became interested in the role played by X→M π-interactions during our studies on the structures and reactivities of the indenylnickel complexes [(1-R‘-Ind)Ni(PPh 3 )(X)] n + (Ind = indenyl; R‘ = H and Me, X = Cl and Me, with n = 0; X = PPh 3 , PMe 3 , and MeCN with n = 1 5 ), including their catalytic activities in the dehydropolymerization of PhSiH 3 . Some of our initial results indicated that the equilibrium stabilities of (Ind)Ni(PPh 3 )(halides) follows the order I > Br > Cl, while the Ni−F derivative could not be prepared .…”
Section: Introductionmentioning
confidence: 99%